Penerapan Peningkatan Hasil belajara Siswa Menggunakan Model Pembelajaran Discovery Learning dengan menerapkan Physics Education Technology (PhET) Berbasis Android - Nur Rahmah; Dahlan Dyru; Nurlansi (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The use of Physics Education Technology (PhET) learning media in the Discovery Learning model, especially in chemistry learning at school, has not been widely implemented by teachers because they do not yet know how PheT is useful in learning. The aim of this research is to determine student learning outcomes with the application of Physics Education Technology (PhET) in the Discovery Learning model on acid-base material and the effectiveness of chemistry learning. The research method used was quasi-experimental with a Pre-test Post test Control Group Design. Data collection techniques were carried out by providing research instruments in the form of essay questions and observation sheets. The results showed that learning chemistry taught by applying Physics Education Technology (PhET) in the Discovery Learning learning model was higher with an average post-test score of 81.23 while the chemistry learning outcomes of students taught by Discovery Learning learning model were lower with an average score the post-test average was only 60.03, and the application of Physics Education Technology (PhET) was quite effective in increasing learning outcomes as indicated by the N-gain of 0.79 which was included in the high category